A Dialectical Perspective on Communication and Ethical Reasoning - Olsen, Richard K. (Christian scholar's review, 2012)
In this essay Julie W. Morgan and Richard K. Olsen explore the utility of a dialectical perspective for approaching and engaging in communication as Christians. After defining dialectics from both historical and critical perspectives, the authors then outline generic dialectics imbedded in almost any communication. The authors draw on the works of Leslie Baxter and...